Rumah Limas Di Museum Balaputera Dewa : Tinjauan Sejarah Dan Peranannya Dalam Pelestarian Budaya - Deliya Paramita, Retno Susanti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2026)
Rumah Limas is a traditional house from South Sumatra that holds not only architectural value but also historical and philosophical significance reflecting the cultural identity of the Palembang community. This study aims to examine the historical journey of Rumah Limas, particularly the one preserved as a collection at the Balaputera Dewa State Museum of South Sumatra, and to analyze its role in cultural preservation. This research employs a qualitative approach with data collected through literature review, observation, and documentation. The findings show that Rumah Limas underwent several relocations due to political and developmental changes before being reconstructed and permanently housed in the museum. Its presence serves as an important medium for cultural education, preservation of traditional values, and reinforcement of local identity. By preserving both the physical structure and its underlying philosophical meaning, Rumah Limas stands not only as a symbol of cultural heritage but also as a means of transmitting cultural knowledge to present and future generations.